Pengaruh Layanan Penguasaan Konten dengan Teknik Modeling Simbolik Terhadap Kebiasaan Belajar - Mutitamah, Ita Pratista; Awalya, Awalya (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
This research based the phenomenon that is obtained from result DCM class V students SD N 4 Ketro Karnagrayung Grobogan that point out study habit problem as big as 31% by criterions D. The purpose for this research was to get information about influence mastery of content service with technique symbolic modelling to study habit. It population is high class students of the SD N 4 Ketro Karnagrayung Grobogan and the sampel of class V was selected using purposive sampling technique. Data collection techniques using study habit questionnaire. Data analysis techniques used that is analysis descriptive percentage and t-test. The result of this research point out there was increase of study habit after be given conduct as mastery of content service with technique symbolic modelling as big as 8,91%. Based result t-test score tcount = 12,59 > ttable = 2,048 or meaning Ha is accepted and Ho is rejected. So, result of this research is mastery of content service with technique symbolic modelling can be influence study habit. Therefore, It is hoped that the teacher as a guide can be more motivate and help student to increase study habit.